The Relationship between Eating Pattern and Eating Behavior in Preschool Children Aged 4-5 Years at Al-Ikhlas - Haerani; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2017)
According to data from the Bulukumba district health office in 2014, there were 44% malnutrition in preschool children and 2015 there was 53% malnutrition in preschool children due to irregular children's eating patterns. The data obtained showed that the incidence of preschool children experiencing malnutrition is increasing from year to year. The purpose of this research is to know the relationship between eating patterns and eating behavior in preschool children aged 4-5 years at Al-Ikhlas Kindergarten, Benteng Gantarang Village, Gantarang District, Research Design using Cross-Sectional. The study population was parents who had children aged 4-5 years in Al-Ikhlas Kindergarten which counted 58 people. A sample of 37 people were taken using consecutive sampling techniques using questionnaire and interview instruments. In AL-Ikhlas Kindergarten, Benteng Gantarang Village, Gantarang District, Bulukumba Regency, 58 students were formed consisting of 2 groups A and B, and after interviews of 20 parents, there were found that there were those who easily ate 8 people and had difficulty eating 12 people. Chi-square test results obtained P = 0.004. This means that there is a significant relationship between eating patterns with eating behavior in preschool children aged 4-5 years at Al-Ikhlas Kindergarten, Benteng Gantarang Village, Gantarang District. It is recommended that parents can provide regular eating patterns to children so that the child's eating behavior becomes good.